Study on the efficiency evolution trend of coordinated development of the human–earth system in minority areas of Yunnan, China - Tai, Lingjuan; Lu, Fen; Huang, Lin; Tian, Furong; Yang, Yun (Frontiers in Ecology and Evolution, 2023)
Improving the development efficiency of human-earth system is a practical requirement for achieving high-quality regional development. The article designs a data envelopment analysis (DEA) model under the constraints of coordinated development degree from the perspective of the interaction of natural, economic and social systems to evaluate the development efficiency of human-earth system and uses GA-BP neural network model for the prediction of the development efficiency of human-earth system of each geographical unit from 2018-2025 based on the panel data of the 8 ethnic autonomous prefectures in Yunnan Province form 1995 to 2017. The study found that from 1995 to 2017, the coordination degree and the coordinated development degree of human-earth system in Yunnan minority areas were on the rise, but mainly manifested in the coordination of low development degree, and the average comprehensive efficiency value of input and output showed a downward trend. The prediction results for 2018-2025 showed that the human-earth system in Yunnan minority areas will be at a low efficient coordinated development level, and the coordinated development degree will show a downward trend. The development degree of natural subsystems in many ethnic minority areas showed negative growth and was negatively correlated with the development degree of economic and social subsystems. In 2025, except Honghe and Banna, the other six regions will be inefficient regions. Among these six inefficient regions, only Wenshan has input redundancy in the natural subsystem, but the phenomenon of input redundancy in the economic subsystem and insufficient output in the natural subsystem is common, indicating that industrial pollution has been controlled to a certain extent in most regions, but the economic investment mode and resource recycling efficiency need to be optimized and improved. Our results could enrich the content of human-earth system characteristics in typical regions, and also provide theoretical support for regional coordinated development in China.